Biomedical and candidate SN P markers of chronopathologies can significantly change affinity of ТАТА -binding protein for human gene promoters - D. A. Rasskazov; N. L. Podkolodnyy; O. A. Podkolodnaya; N. N. Podkolodnaya; V. V. Suslov; L. K. Savinkova; P. M. Ponomarenko; M. P. Ponomarenko (Вавиловский журнал генетики и селекции, 2016)
Computational analysis of millions of unannotated SNPs from the 1000 Genomes Project may speed up the search for biomedical SNP markers. We combined the analysis of SNPs in the binding sites of ТАТА - binding protein (ТВР) using a previously described W eb service (http://beehive.bionet.nsc.ru/cgi-bin/mgs/ tatascan/start.pl) with a keyword search for biochemicalmarkers of chronopathologies, which correspond to clinical manifestations of these SNPs. In the [–70; –20] region of promoters of 14 human genes (location of proven binding sites of ТВР), we found 32 known and candidate SNP markers of circadian- rhythm disturbances, including rs17231520 and rs569033466 (both: risk of chronopathologies in liver); rs35036378 (behavioral chronoaberrations); rs549858786 (rheumatoid arthritis with a chronoaberration of IL1B expression); rs563207167, rs11557611, and rs5505 (all three: chronopathologies of the tumor – host balance, blood pressure, and the reproductive system); rs1143627 (bipolar disorder with circadian dependence of diagnosis and treatment); rs16887226 and rs544850971 (both: lowered resistance to endotoxins because of the imbalance between the circadian and immune systems); rs367732974 and rs549591993 (both: circadian dependence of heart attacks); rs563763767 (circadian dependence of myocardial infarction); rs2276109 and rs572527200 (both: circadian dependence of asthma attacks); rs34223104, rs563558831, and rs10168 (circadian optima of treatment with methotrexate and cyclophosphamide); and rs397509430, rs33980857,rs34598529, rs33931746, rs33981098, rs34500389, rs63750953, rs281864525, rs35518301, and rs34166473 (all: neurosensory hearing loss and restless legs syndrome). For these SNPs, we evaluated α (significance) of changes in the affinity of ТВР for promoters, where increased affinity corresponds to overexpression of the genes, and decreased affinity to deficient expression (Z-test). Verification of these 32 SNP markers according to clinical standards and protocols may advance the field of predictive preventive personalized medicine.